Post-Pandemic Economic Resilience: The Role of Women-Led SMEs in Tasikmalaya's Craft Sector, West Java - Yunia Dwie Nurcahyanie; Adelia Azzahra (Politeknik Siber Cerdika Internasional, 2025)
This qualitative research investigates the mechanisms of economic resilience in the post-COVID-19 era through a study of women-led small and medium-sized enterprises in the handicraft sector of Tasikmalaya. Data collection was carried out through in-depth interviews with 20 female entrepreneurs and field observations. To complement the qualitative analysis, basic quantitative descriptive statistics were derived from structured interview responses. The findings demonstrate that these enterprises have successfully navigated unexpected challenges by adopting smart adaptation strategies. The descriptive data reveal that social networks and digital platforms were utilized for sales by 80% of respondents, while 55% actively participated in local collaboration networks. Regarding coping strategies, cost optimization was adopted by 90% of the enterprises, while 70% diversified their products. However, only 35% of the enterprises have returned to pre-crisis income levels, while 45% remain on the path to sustainable recovery. The product mix has shifted from 75% purely traditional products to 60%, while the share of applied and customized products has increased correspondingly. This research demonstrates how resilience in these enterprises emerges from social capital, collective wisdom, and innovation in practice rather than from institutional support. The study highlights the importance of formulating targeted support policies aligned with the unique characteristics of these firms. Recommendations include strengthening local cooperation networks, providing access to financial resources, and developing training programs responsive to entrepreneurs' needs.